Does the Stocklab Game Increase Students’ Understanding on Stock Markets? - Muhammad Abdul Ghofur; Nuzuliya Rohma Qurrota Agyun (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2019)
This study aimed to analyze the use of stocklab game to improve students' understanding of the stock market. This research was a quasi-experimental study with a nonequivalent control group design. The object of this study were students of class X IPS in MAN Surabaya. Class X IPS 2 was determined as the experimental class while class X IPS 3 as the control class. Both classes were given the same treatment using cooperative learning methods make a match type and numbered head together, however in the experimental class, games were given in the form of stocklab games. The analysis technique used to test the research hypothesis was one way ANOVA. Hypothesis tested by comparing the pre-test and post-test scores in both classes. Based on the analysis results, it was known that there were differences in students' understanding of the control class and the experimental class, where the understanding of the experimental class students tend to be better than students in control class. In addition, students also tend to understand more stock market terms.